Suspended Attitudes: Exclusion and Emotional Disengagement from School. Issue 1 (January 2019) - Pyne, Jaymes
We know far less about the unintended social-psychological consequences of out-of-school suspensions on students than we do of the academic, behavioral, and civic consequences. Drawing on theories of socialization and deviance, I explore how suspension events influence students' emotional engagement in school through changes in their attitudes. Using longitudinal middle school survey data connected to individual student administrative records, I find that students who receive out-of-school suspensions are psychologically vulnerable prior to their removal from school. Accounting for demographic characteristics of students, prior year disciplinary involvement, and students' beginning-of-year attitudes, I find suspensions might further harm students by negatively changing their academic identities and perceptions of adults in school. A series of robustness checks add nuance and strengthen the claims I infer from the main analyses. I close by discussing how the engagement-related consequences of suspension inform social theory and educational policy.